Answer:
[tex]v_f = \sqrt{(\frac{L_w}{t} + \frac{1}{2}gt)^2 + 2gh_b}[/tex]
Explanation:
As we know that pot is visible to us for "t" time
so here we have
[tex]L_w = (\frac{v_b + v_o}{2})t[/tex]
here we know that
[tex]v_b[/tex] = speed at the bottom of the window
[tex]v_o[/tex] = speed at the top of the window
[tex]v_b + v_o = \frac{2L_w}{t}[/tex]
now we will have
[tex]v_b - v_o = gt[/tex]
so we can say
[tex]2v_b = \frac{2L_w}{t} + gt[/tex]
[tex]v_b = \frac{L_w}{t} + \frac{1}{2}gt[/tex]
now velocity of the pot just before it hit the floor is given as
[tex]v_f^2 - v_i^2 = 2 a d[/tex]
[tex]v_f^2 - (\frac{L_w}{t} + \frac{1}{2}gt)^2 = 2(g)(h_b)[/tex]
[tex]v_f^2 = (\frac{L_w}{t} + \frac{1}{2}gt)^2 + 2gh_b[/tex]
so we have
[tex]v_f = \sqrt{(\frac{L_w}{t} + \frac{1}{2}gt)^2 + 2gh_b}[/tex]